The Bureaucracy of Murder Revisited - Breton, Albert; Wintrobe, Ronald (Journal of Political Economy, 1986)
The paper reexamines the question of the guilt of subordinates in large organizations, a question posed with special force by Hannah Arendt in her book on Adolf Eichmann. He consistently claimed innocence on the ground that he was only following orders. Arendt accepted this picture of the regime but nevertheless indicted him for "crimes against humanity." The paper suggests that this model of the Nazi bureaucracy is false: in the Nazi bureaucracy of murder, as in other large bureaucracies, subordinates competed with each other to advance the goals of superiors they trusted. In this context, their guilt is easily established.